Effect of Season and High Ambient Temperature on Activity Levels and Patterns of Grizzly Bears (Ursus arctos) - McLellan, Michelle L. (PLoS One, 2015)
Understanding factors that influence daily and annual activity patterns of a species provides insights to challenges facing individuals, particularly when climate shifts, and thus is important in conservation. Using GPS collars with dual-axis motion sensors that recorded the number of switches every 5 minutes we tested the hypotheses: 1. Grizzly bears (Ursus arctos) increase daily activity levels and active bout lengths when they forage on berries, the major high-energy food in this ecosystem, and 2. Grizzly bears become less active and more nocturnal when ambient temperature exceeds 20°C. We found support for hypothesis 1 with both male and female bears being active from 0.7 to 2.8 h longer in the berry season than in other seasons. Our prediction under hypothesis 2 was not supported. When bears foraged on berries on a dry, open mountainside, there was no relationship between daily maximum temperature (which varied from 20.4 to 40.1°C) and the total amount of time bears were active, and no difference in activity levels during day or night between warm (20.4–27.3°C) and hot (27.9–40.1°C) days. Our results highlight the strong influence that food acquisition has on activity levels and patterns of grizzly bears and is a challenge to the heat dissipation limitation theory.